The Finno-Karelian bear feast and wedding : The bruin as a guest of honour of the village - Piludu, Vesa Matteo (2024)
This chapter aims to analyse the second stage of Finnish and Karelian bear ceremonialism – the songs and rituals performed during the bear feast in the village of the hunters. The feast in which the bear meat was eaten received a ritual “voluntary visit” of the bruin to the village. During the bear feast, the killed bruin was treated as a groom or a guest of honour participating in a marriage or a drinking party: The hunters stressed the humanlike features of the bear to accomplish a successful ritual exchange. The introduction of the killed bear into the village was even presented as the bear’s wedding, representing a partial and mimetic unification of the people of the forest with the human community. However, the people never forgot the potential dangerousness of the entrance of the bear into the village, or the bear’s alterity. The arrival of the killed bear in the village resembled its attack on cattle, so the hunters encouraged the young women to protect the cows. The bear feast reveals the complexity of the relationship between bears and women, who sometimes refused to eat bear meat. Bringing home killed game animals, and in particular the bear, could cause supernatural illnesses. To avoid these risks, the bear was pleased with songs and offerings of ale, and the eating of the meat and organs was made possible by performing protective rituals. Particularly important was the ritual of eating the powerful organs of the head of the bear (the ears, eyes and tongue), connected to a deep form of bodily and spiritual communion between humans and bears. Peer reviewed